PENGGUNAAN MEDIA PEMBELAJARAN APLIKASI WORDWALL UNTUK MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK PADA PEMBELAJARAN FISIKA DI SMA - Febrianti Utami; Widya Bratha Sheftyawan; Ardian Yoga Pratama; Bambang Supriadi (JURNAL PEMBELAJARAN FISIKA, 2023)
The lack of motivation of students due to physics learning tends to be saturated with the many formulas taught and the use of learning media by teachers who do not attract the attention of students underlies this research. This research focuses to determine whether the use of wordwall media in Physics class can increase students' learning motivation. This study uses a classroom action research method, which includes pre-learning cycles and learning cycles I and II using quantitative descriptive analysis. The research was conducted on 35 students of class X-3 at SMA Negeri 5 Jember. Data collection was conducted using questionnaires and observation, which categorised students into five groups based on their motivation level. The results showed that the use of wordwall application learning media had a significant positive effect on student motivation, which resulted in an increase in motivation in the very high and high learning motivation categories in learning cycles I and II. The study also found an increase of 37.14% with 13 students in the very high learning motivation category and an increase of 54.29% with 21 students in the high learning motivation category after the application of wordwall application in Physics learning.